Faith-Based Coping Among Arabic-Speaking Refugees Seeking Mental Health Services in Berlin, Germany: An Exploratory Qualitative Study - Rayes, Diana; Karnouk, Carine; Churbaji, Dana; Walther, Lena; Bajbouj, Malek (Frontiers in Psychiatry, 2021)
Background: The benefits of faith-based coping or using religious and spiritual beliefs as a stabilizing force for interpreting stressful or distressing events are largely unexplored among the exodus of Arabic-speaking refugee populations from Muslim-majority countries, particularly those resettled in Europe. The present study aimed to explore the manifestation of faith-based coping strategies among Arabic-speaking refugee adults seeking mental healthcare services in Berlin, Germany and explore how favorable faith-based coping strategies can be optimized from a mental health service-delivery and broader integration perspective. Methods: A total of 17 qualitative interviews were conducted with Arabic-speaking refugee adults (6 females, 11 males) seeking mental health services at the Charité Universitaetsmedizin in Berlin. Research questions aimed to solicit comprehensive perspectives from refugee communities on their mental health, with an emphasis on faith-based coping, and how this facilitated or impeded their integration into German society. Interview transcripts were translated to English from Arabic and analyzed using MAXQDA (2018) to highlight thematic patterns using a grounded theory approach. Results: Findings were structured into four themes, including: (I) faith-based coping methods during flight, (II) changes in faith practices upon arrival (III) faith-based coping methods to address distress during integration, and (IV) advice for German mental health providers. Participants who demonstrated a stronger commitment to faith were more likely to utilize faith-based coping strategies when seeking mental health services and facing the challenges of displacement and integration. Examples of faith-based coping included prayer, supplication, reciting scripture, and seeking help from a local religious leader. Conclusion: The findings suggest how faith and faith practices play a significant role in the mental health and integration of refugee populations in Germany and provides insight on how mental health care can be delivered in a culturally-sensitive manner, providing alternatives to the social, cultural and linguistic barriers posed by the German health system. These findings are particularly relevant for mental health professionals, non-governmental organizations and humanitarian aid agencies providing mental health care to Arabic-speaking populations recently resettled in Western contexts.